Formalisasi Hukum Islam Kedalam Tata Hukum Indonesia - Tomi Agustian (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2019)
Islamic law is one of the raw materials for the national legal systems in addition to the customary law and the law of the West.Therefore Islamic law can be used as raw material for the construction of the device, order and culture of origin of national law does not conflict with the values of Pancasila and the 1945 CONSTITUTION and in accordance with the needs of the people of Indonesia law.Can not be contradicted by evidence of any kind that Islamic law has an important and strategic position in national law drafting and pmbentukan Indonesia One of the efforts to incorporate Islamic law into the national laws of grammar through transformation.This paper discusses about the effort will be the transformation of Islamic law into the law of Indonesia governance. the formalization of Islamic law if done substantively, cannot be released and must be preceded by a reference to the judiciary with constitutional considerations and the history of the nation. The process is inseparable from the history of Islamic law in Indonesia, and the policy of Indonesian legal politics in placing the position of Islamic law in the national legal system.